1989
DOI: 10.1038/bjc.1989.90
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in a T3 bladder cancer trial

Abstract: model (Cox, 1972) was assumed. Here, the term 'hazard' refers mainly to the mortality rate. The only exception is when adjustment was made for natural mortality in evaluating the prognostic value of age and sex when a proportional 'excess mortality' model was used, i.e. mortality in excess of that expected in a group of the same age and sex composition in the general population. The latter was estimated using the 1984 rates for England and Wales (OPCS, 1985). The long duration of the trial and the relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In our research there was no important variations in OS or DFS between SCC and TCC where five years, and 5 years, DFS for TCC was 8% versus 7% for SCC with (P-value 0.795) and OS for TCC was 13.2% versus 12% for SCC with (P-value 0.783). The poor performance of large primary tumors has been reported by Babiker A et al (11) who found that the presentation size of the primary tumor was the single most significant prognostic factor. The mortality rates for small, moderate and large tumors were mean, in the ratios 1:1.5:2 respectively (11) .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our research there was no important variations in OS or DFS between SCC and TCC where five years, and 5 years, DFS for TCC was 8% versus 7% for SCC with (P-value 0.795) and OS for TCC was 13.2% versus 12% for SCC with (P-value 0.783). The poor performance of large primary tumors has been reported by Babiker A et al (11) who found that the presentation size of the primary tumor was the single most significant prognostic factor. The mortality rates for small, moderate and large tumors were mean, in the ratios 1:1.5:2 respectively (11) .…”
Section: Discussionmentioning
confidence: 78%
“…The absence of survival statistics in our research may be ascribed to the fact that our patients appeared at later stages and that many of them were lost to follow-up. Amiri et al (10) demonstrated that patients with bladder cancer survival rate versus age at diagnosis showed that the five-year survival in participants ≥ 65 year is lower than the others (11) . While Babiker A et al (11) demonstrated no important relation between OS and the patients age at the diagnosis time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle-invasive bladder cancer is an aggressive tumor that was associated with a median survival of 22 months in the 1980s (Babiker, Shearer, & Chilvers, 1989). Patients with muscle-invasive disease have a 50 to 65% overall survival rate in the modern era (C. N. Sternberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Provisional TNM staging with the imaging technique, along with detection of distant metastatic lesions in the liver (M stage), is clinically valuable because advanced TNM stage in human bladder tumor patients is closely associated with short‐survival times . Recently, in addition to these imaging findings used for TNM staging, ultrasonographic characteristics such as tumor size, shape, and echogenicity have also been described as factors for predicting prognosis …”
Section: Introductionmentioning
confidence: 99%